Patient Safety: the nurse’s role in quality control in the surgical center (Research, Society and Development, 2022)
Objective: To discuss the role of nurses in the quality control of the operating room, to promote patient safety. Methodology: This study is characterized as descriptive research with a qualitative approach, based on the search for scientific articles in the data platforms: Latin American and Caribbean Literature on Health Sciences (LILACS), National Library of Medicine – PUBMED and Scientific Electronic Library Online – SCIELO, published between 2017 and 2022. Results: 14 scientific articles were selected for the final sample, where it was possible to observe that the safe surgery checklist is the most important to be performed as a behavior of the nurse and the rest of the nursing team, and that they recognize the importance of patient safety. Final Considerations: The present study emphasizes the importance of nurses in organizing this care, ensuring that the professionals of the nursing team carry out the Patient Safety protocol, and in the Surgical Center they can apply the Safe Surgery regulations, thus using the Safety Checklist. Safe Surgery, following the standardization of the World Health Organization (WHO).